Algunas consideraciones en torno a la figura del líder tribal caldeo (s. IX-VIII a.n.e.) - Vidal, Jordi (Gerión. Revista de Historia Antigua, 2008)
Some remarks about the figure of the Chaldean tribal chief (9th-8th centuries BCE). The paper analyses the figure of the Chaldean tribal chief represented in 9th-8th centuries BCE Assyrian documents. The study undertaken reveals the considerable level of economic, political and military power held by Chaldean leaders, but it also illustrates the survival of tribal structures and traditions that limited the exercise of those powers.